2021
DOI: 10.1002/evl3.205
|View full text |Cite
|
Sign up to set email alerts
|

Morning glory species co-occurrence is associated with asymmetrically decreased and cascading reproductive isolation

Abstract: Hybridization between species can affect the strength of the reproductive barriers that separate those species. Two extensions of this effect are (1) the expectation that asymmetric hybridization or gene flow will have asymmetric effects on reproductive barrier strength and (2) the expectation that local hybridization will affect only local reproductive barrier strength and could therefore alter within‐species compatibility. We tested these hypotheses in a pair of morning glory species that exhibit asymmetric … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 99 publications
(88 reference statements)
0
13
0
Order By: Relevance
“…In Capsella , different effective ploidy resulted in endosperm-based reproductive barriers ( Lafon-Placette et al , 2018 ). Rapid evolution of HSF has also been revealed among closely related species of Ipomoea ( Ostevik et al , 2020 ) and Clarkia ( Briscoe Runquist et al , 2014 ).…”
Section: Introductionmentioning
confidence: 98%
“…In Capsella , different effective ploidy resulted in endosperm-based reproductive barriers ( Lafon-Placette et al , 2018 ). Rapid evolution of HSF has also been revealed among closely related species of Ipomoea ( Ostevik et al , 2020 ) and Clarkia ( Briscoe Runquist et al , 2014 ).…”
Section: Introductionmentioning
confidence: 98%
“…While hard to disentangle from other reproductive barriers, the asymmetry in hybridization and backcrossing found here suggest that fertilization opportunities may have had a strong role in shaping the direction of gene flow between the mangrove killifish species. In addition to influencing the degree of reproductive isolation between sympatric species, asymmetrical introgression can also affect the reproductive compatibility within species between allopatric and sympatric populations, if the latter are experiencing asymmetrical introgression [71]. Further studies are needed to investigate whether the asymmetric gene flow of K. hermaphroditus genome into K. ocellatus in the hybrid zones has impacted the reproductive isolation between allopatric vs sympatric K. ocellatus populations.…”
Section: Discussionmentioning
confidence: 99%
“…Another important aspect of the dynamics of population divergence and speciation, often underappreciated in theoretical studies but increasingly reported by empirical research, is that migration of individuals is commonly found to be asymmetrical between populations and species. This pattern is observed across multiple spatial scales and across taxa including plants [7,[22][23][24], fish [25][26][27], birds [28], and insects [29]. As well, meta-populations studies within species document general asymmetric migration patterns where the net movement of individuals between any two subpopulations is typically non-zero and where subpopulations vary in size in tandem with rates of immigrants/emigration.…”
Section: Introductionmentioning
confidence: 93%
“…Both Nosil and Yukilevich [10] and Kyogoku and Kokko [21] predict habitat isolation and sexual isolation could evolve within a single study system under reinforcing selection; however, neither model examined the effect of asymmetric migration on the evolvability of multiple prezygotic reproductive isolating mechanisms. Asymmetric migration within and between species is a common phenomenon across different taxa [22][23][24][25][26][27][28][29]. Therefore, we stress the need for both theoretical and empirical studies to test the generality of asymmetric reinforcement in driving the asymmetry in the direction of habitat isolation and sexual isolation.…”
Section: Comparing Data With Models: Evolution Of Habitat and Sexual Isolation Via Reinforcementmentioning
confidence: 99%